Cover Feature: Phthalimide‐Based Transparent Electron‐Transport Materials with Oriented‐Amorphous Structures: Preparation from Solution‐Processed Precursor Films (ChemPlusChem 9/2019). Issue 9 (18th July 2019) - Nakamura, Tomoya; Shioya, Nobutaka; Hasegawa, Takeshi; Murata, Yasujiro; Murdey, Richard; Wakamiya, Atsushi
Abstract : The cover feature shows the solid‐state thermal conversion of the star‐shaped, triazine‐based Tris‐TrPIBoc precursor to Tris‐TrPIH through the release of tert ‐butoxycarbonyl (Boc) substituent groups. Tris‐TrPIH, which contains three phthalimide moieties connected to a triazine core, forms hydrogen‐bonded networks connected through the points of each star. The resulting network is envisioned as a flat‐lying hexagonal sheet with an "oriented‐amorphous" structure. Details are given in the Full Paper by T. Hasegawa, A. Wakamiya and co‐workers on page 1396 in Issue 9, 2019 (DOI: 10.1002/cplu.201900274 ).